Spatial Pattern and Influencing Factors of Tourist Attractions in Coastal Cities: A Case Study of Qingdao - Yue Xu; Xuliang Zhang; Kuncheng Zhang; Jing Yu; Jia Liu (ISPRS International Journal of Geo-Information)
The spatial distribution of tourist attractions plays a critical role in the development of coastal cities. Qingdao, with its coastal geography, rich cultural heritage, and rapid urbanization, serves as a representative case. This study integrates POI and multi-source data, employing methods such as the average nearest neighbor index, kernel density estimation, standard deviational ellipse, and Geodetector to analyze the spatial characteristics and influencing factors of Qingdao’s tourist attractions. Additionally, path dependence theory is innovatively applied to elucidate the mechanisms of the city’s development trajectory. Both natural and social factors influence this distribution, where the resource environment forms the foundational basis, the economic development provides impetus, and the urban development orientation exerts a regulatory effect. The findings are broadly applicable to other coastal tourist cities and offer strategic insights for sustainable development in such contexts.